Calcium-Activated Chloride Channels in Myometrial and Vascular Smooth Muscle - Wray, Susan; Prendergast, Clodagh; Arrowsmith, Sarah (Frontiers in Physiology, 2021)
In smooth muscle tissues Calcium-activated chloride channels provide the major anionic channel. Opening of these channels leads to chloride efflux and depolarization of the myocyte membrane. In this way, activation of the channels by a rise of intracellular [Ca2+], from a variety of sources, produces increased excitability and can initiate action potentials and contraction or increased tone. We now have a good mechanistic understanding of how the channels are activated and regulated, due to identification of TMEM16A (ANO1) as the molecular entity of the channel, but key questions remain. In reviewing these channels and comparing two distinct smooth muscles, myometrial and vascular, we expose the differences that occur in their activation mechanisms, properties, and control. We find that the myometrium only expresses “classical”, Ca2+-activated, voltage sensitive channels, whereas both tonic and phasic blood vessels express classical, and non-classical, cGMP-regulated Ca2+-activated chloride channels, which are voltage insensitive. This translates to more complex activation and regulation in vascular smooth muscles, irrespective of whether they are tonic or phasic. We therefore tentatively conclude, that although these channels are expressed and functionally important in all smooth muscles, they are probably not part of the mechanisms governing phasic activity. Recent knockdown studies have produced unexpected functional results, e.g., no effects on labour and delivery, and tone increasing in some but decreasing in other vascular beds, strongly suggesting that there is still much to be explored concerning Ca2+-activated chloride channels in smooth muscle.